2019
DOI: 10.1177/1098612x19840090
|View full text |Cite
|
Sign up to set email alerts
|

CT characterisation of feline adrenal glands

Abstract: Objectives The objectives of this study were to describe the CT characteristics of the adrenal glands in healthy cats, to provide normal reference biometry for adrenal gland size and attenuation values, and to investigate the association with age, sex, laterality and body weight. Methods Retrospective evaluation of 30 CT studies of healthy adult cats recruited from September 2013 to July 2015 was performed. Healthy cats >1 year of age were included based on the absence of clinical signs, unremarkable physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One study retrospectively assessed CT images of adrenal gland size in healthy cats, and no association was found between body weight and adrenal gland size in 30 cats. 12 Similarly, another study reported no correlation between adrenal thickness and body weight, and between adrenal thickness and body surface area in diseased cats. 10 In one study, most of the adult cats (82%) weighed >4 kg, whereas only 18% weighed <4 kg.…”
Section: Introductionmentioning
confidence: 97%
“…One study retrospectively assessed CT images of adrenal gland size in healthy cats, and no association was found between body weight and adrenal gland size in 30 cats. 12 Similarly, another study reported no correlation between adrenal thickness and body weight, and between adrenal thickness and body surface area in diseased cats. 10 In one study, most of the adult cats (82%) weighed >4 kg, whereas only 18% weighed <4 kg.…”
Section: Introductionmentioning
confidence: 97%
“…Visibility, attenuation, location, anatomic landmarks, and size were registered for each organ. Attenuation values of the coelomic organs were measured in Hounsfield units (HUs), using a circular/ovoid region of interest (ROI) on the images of every organ following the same protocol previously used in small animals ( Bertolini et al , 2006 ; Mallol et al , 2020 ). One measurement was performed for each organ in the precontrast and postcontrast study.…”
Section: Methodsmentioning
confidence: 99%
“…They measured 12–18 mm in length for the right ( Figure 5 ) and left ( Figure 6 ) adrenal glands, respectively, and 6.2 mm at the maximum height (reported reference range: length 11.6 ± 2.1 mm and height 6.1 ± 1.3 mm in normal cats). 3 Bilateral chronic renal changes (slight asymmetry and undulated margin) were also noted that were suggestive of chronic kidney disease. From the results of these diagnostic tests, a diagnosis of pituitary-dependent hyperadrenocorticism (HAC) was made.…”
Section: Case Descriptionmentioning
confidence: 99%